When Ellie cheated: My Little Life - "Oldfield, Jenny" (Hodder Children's: London, 2002)
Tiffany Little is a girl with attitude and a diary she's not afraid to use. Full of all the things girls worry about, like school, friends and shopping, Tiffany's diary is her way of preparing for being a mega famous blockbusting author
Keywords: Diary fiction-Children's stories